Application of the R-peak detection algorithm for locating noise in ECG signals. (February 2022) - Tomas, Božo; Grabovac, Mijo; Tomas, Karlo
Highlights: Detection of real R-peaks using the original ECG signal. Detection of both real and false R-peaks using a resampled ECG signal. Locating noise in an ECG signal by locating false R-peaks. Abstract: This paper proposes a novel and straightforward algorithmic solution for locating noise in an ECG signal. The algorithm discovers noise in the ECG signal by applying the R-peak detection algorithm at different sampling rates. The authors observed that false R-peaks appear disproportionately in noise-contaminated parts of resampled ECG signals. Therefore, locating false R-peaks can indicate the noise-contaminated segments of the ECG signals. The main aim of this paper is presenting a new idea for ECG noise detection but the paper is not meant to discuss the origin nor the characterization of the said noises detected by the proposed algorithm. However, the paper shows that the parameter "frequency of false R-peaks" doesn't have the same numerical value for different ECG noises. Hence, this parameter can do noise clasification. The algorithm is easy to follow, and the results demonstrate its performance.